Development and implementation of the Rhinoceros DNA Index System (RhODIS®) for the forensic analysis and biological management of African rhinoceros - Thompson, P.N. (Peter N.) (University of Pretoria, 2025)
Thesis (PhD (Veterinary Sciences))--University of Pretoria, 2018.